2017
DOI: 10.1186/s13052-017-0432-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring adherence to guidelines of antibiotic use in pediatric pneumonia: the MAREA study

Abstract: BackgroundChildren are the most vulnerable population exposed to the use of antibiotics often incorrectly prescribed for the treatment of infections really due to viruses rather than to bacteria. We designed the MAREA study which consisted of two different studies: i) a surveillance study to monitor the safety/efficacy of the antibiotics for the treatment of pneumonia (CAP), pharyngotonsillitis and acute otitis media in children younger than 14 yrs old, living in Liguria, North-West Italy and ii) a pre−/post-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
1
21
1
1
Order By: Relevance
“…However, this might not be valid in the Italian Healthcare System, where each child is assigned to a primary care pediatrician, which is the primary referral for any health-related matters, thus guaranteeing continuity in the patient’s care. Nonetheless, our results align with the literature findings in a similar setting, with a high BS-ATs rate prescribed for LRTI [ 18 , 19 ]. Other key drivers for BS-ATs prescriptions might be represented by the young age and by the lack of pneumococcal vaccination and non-normal laboratory findings [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, this might not be valid in the Italian Healthcare System, where each child is assigned to a primary care pediatrician, which is the primary referral for any health-related matters, thus guaranteeing continuity in the patient’s care. Nonetheless, our results align with the literature findings in a similar setting, with a high BS-ATs rate prescribed for LRTI [ 18 , 19 ]. Other key drivers for BS-ATs prescriptions might be represented by the young age and by the lack of pneumococcal vaccination and non-normal laboratory findings [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Community-acquired pneumonia (CAP) is a highly prevalent infection and remains the first cause of early childhood mortality in developing countries (1)(2)(3). Scientific guidelines were established to optimize and standardize medical care yet, several authors reported discrepancies between recommendations and actual management (4)(5)(6)(7)(8), leading to overuse of antibiotics, a higher resistance rate in community-acquired pathogens (9), and longer hospitalizations (7). This study aims to evaluate our local inpatient practices in children with CAP and to identify clinical parameters likely to influence adherence to guidelines, in order to better understand eventual gaps in our medical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The treating doctor in Sudan using different regimen like penicillin which is recommended by WHO which is cheap and available, Augmentin, b-lactam inhibitors), (which is more expensive and ceftriaxone which is expensive. the Sudanese experience showed no signi icant difference in recovery rate regardless of the drug [23,[31][32][33]. Finally, many studies recommended zinc sulfate with the antibiotic, regardless of the type will minimized hospital stay [34].…”
Section: Discussionmentioning
confidence: 99%